Synthesis of 3,7-Dinitro-1,3,5,7-tetraazabicyclo-[3,3,1]nonane (DPT) Using Task-Specific Ionic Liquids as Recoverable Catalysts - L. I. U. Xiao Bing; L. U. Ming (E-Journal of Chemistry)
A facile and efficient method for the synthesis of 3,7-dinitro-1,3,5,7-tetraazabicyclo[3,3,1]nonane (DPT) has been developed starting from urea. In the procedure some task-specific ionic liquids was synthesized as a cheap and recyclable catalyst for the synthesis of DPT. The catalysts could be recovered and reused several times without noticeably decrease in the catalytic activity.